Strategic Approach to the Globalization of Sasang Constitutional Medicine - Lee, Myeong Soo (Hindawi Publishing Corporation, 2011)
The workshop on “Strategic Approach to the Globalization of Sasang Constitutional Medicine (SCM)” was held in the Korea Institute of Oriental Medicine (KIOM) on September 18, 2009. This workshop was designed to discuss and brainstorm the strategic approach to the globalization of SCM, one of the unique systems in Korean Traditional Medicine, with three topics and an extensive panel discussion. Professor Edwin Cooper, Editor-in-Chief of eCAM, gave a commemorative lecture for publication of the second supplement of eCAM entitled “Sasang Constitutional Medicine as a Holistic Tailored Medicine”. The other two presenters suggested some practical methods for globalization of SCM on the basis of their experiences. After the three main presentations, there was a panel discussion session for further development of workshop topics, extended by five other external experts. They discussed the benefits, limitations and essentials for globalization of Korean Traditional Medicine, specifically SCM, from bench to bedside.